VITAMINS ARE THE MAIN COMPONENT OF NUTRITION IN THE DIET OF CLIMACTERIC WOMENS - Saidova Gulbakhor Tursunalievna; Tursunova Nigora Anvarovna; Mirsidiqova Nigoraxon Mirusmonovna (Journal Park Publishing, 2026)
During the climacteric period, it is necessary to monitor adequate intake of vitamins, as well as macro- and microelements, which are biologically active substances. Vitamins belong to the group of regulatory substances involved in the normalization of metabolism and the regulation of metabolic processes. They act as biological catalysts of chemical reactions occurring in the body. Another important function of vitamins is their coenzyme role, participation in enzyme formation, and involvement in the functioning of enzymatic systems.
Keywords: Metabolic processes, metabolism, biologically active supplements, proper and balanced dietary regimen, diseases.